2023
DOI: 10.3390/ijms24087633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-(Pyridin-2-yl)quinazolin-2,4(1H,3H)-diones via Annulation of Anthranilic Esters with N-pyridyl Ureas

Abstract: A new route for the synthesis of quinazolin-2,4(1H,3H)-diones and thieno [2,3-d]pyrimidine-2,4(1H,3H)-diones substituted by pyridyl/quinolinyl moiety in position 3 has been developed. The proposed method concluded in an annulation of substituted anthranilic esters or 2-aminothiophene-3-carboxylates with 1,1-dimethyl-3-(pyridin-2-yl) ureas. The process consists of the formation of N-aryl-N′-pyridyl ureas followed by their cyclocondensation into the corresponding fused heterocycles. The reaction does not require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…[75,76] Moreover, it has found that such ureas are able to react with N-and O-nucleophiles acted like masked hetaryl isocyanates. [77][78][79][80] We hypothesized that involving N-oxides of these ureas into similar transformations can be a good "late-stage modification" approach to rise the diversity of azine-N-oxides. The results of this study are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…[75,76] Moreover, it has found that such ureas are able to react with N-and O-nucleophiles acted like masked hetaryl isocyanates. [77][78][79][80] We hypothesized that involving N-oxides of these ureas into similar transformations can be a good "late-stage modification" approach to rise the diversity of azine-N-oxides. The results of this study are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%